P048: Current practices of management for mild traumatic brain injuries with intracranial hemorrhage. (May 2019) - Fortier, É.; Paquet, V.; Émond, M.; Chauny, J.; Hegg, S.; Malo, C.; Carmichael, P.; Champagne, J.; Gariepy, C.
Abstract : Introduction : The radiological and clinical follow-up of patients with a mild traumatic brain injury (mTBI) and an intracranial hemorrhage (ICH) is often heterogeneous, as there is no official guideline for CT scan control. Furthermore, public sector health expenditure has increased significantly as the number of MRI and CT scan almost doubled in Canada in the last decade. Therefore, the main objective of this study was to describe the current management practices of mTBI patients with intracranial hemorrhage at two level-1 trauma centers.Methods : Design: An historical cohort was created at the CHU de Québec – Hôpital de l'Enfant-Jésus (Québec City) and Hôpital du Sacré-Coeur (Montréal). Consecutive medical records were reviewed from the end of 2017 backwards until sample saturation using a standardized checklist.Participants : mTBI patients aged ⩾16 with an ICH were included.Measures : The main and secondary outcomes were the presence of a control CT scan and neurosurgical consultation/admission.Analyses : Univariate descriptive analyses were performed. Inter-observer measures were calculated.Results : Two hundred seventy-four patients were included, of which 51.1% (n = 140) came from a transfer. Mean age was 60.8 and 68.9% (n = 188) were men. Repeat CT scan was performed in 73.6% (n = 201) of our patients as 12.5% showed a clinical deterioration. The following factors might have influenced clinician decision to proceed to a repeat scan: anticoagulation (association of 87.1% with scanning; n = 27), antiplatelet (84.1%; 58), GCS of 13 (94.1%; 16), GCS of 14 (75%; 72) and GCS of 15 (70.2%; 111). 93.0% (n = 254) of patients had a neurosurgical consultation and only 6.7% (17) underwent a neurosurgical intervention.Conclusion : The management of mild traumatic brain injury with hemorrhage uses a lot of resources that might be disproportionate with regards to risks. Further research to identify predictive factors of deterioration is needed.